Discussion on the Success Stories of Female CEOS Have Changed the Magnitude of Commerce Worldwide - Farhathullah Khan, K. Sindhura (Journal of Informatics Education and Research, 2024)
The research article evaluates the success stories of the female CEOs who have created transformation in the business practices. Moreover, the Lack of diversity in the workplaces is evaluated to understand the need of gender equality practices in the workplace for organisational growth. Literature review has been formulated to discuss the past researchers’ ideas on the targeted phenomenon. Contingency theory of leadership has been evaluated for encouraging the young professionals towards taking decision in the firm to identify the customer’s demand. Secondary qualitative method helps to create a thematic analysis evaluating the key works of the study. A brief discussion has been given to examine the usefulness of the themes for improving organisational performance.